The prevalence and impact of Babesia canis and Theileria sp. in free-ranging grey wolf (Canis lupus) populations in Croatia - Beck, Ana; Huber, Doroteja; Polkinghorne, Adam; Kurilj, Andrea Gudan; Benko, Valerija; Mrljak, Vladimir; Reljić, Slaven; Kusak, Josip; Reil, Irena; Beck, Relja (Parasites & Vectors, 2017)
Background: Babesia spp. and Theileria spp. are important emerging causes of disease in dogs. Alongside these domesticated hosts, there is increasing recognition that these piroplasms can also be found in a range of wild animals with isolated reports describing the presence of these pathogen in foxes ( Vulpes vulpes ) and captive grey wolves ( Canis lupus ). The prevalence and impact of these infections in free-ranging populations of canids are unknown. To gain a better insight into the epidemiology and pathogenesis of piroplasm infections in free-ranging grey wolves, pathological and molecular investigations into captive and free-ranging grey wolves in Croatia were performed. Results: The carcasses of 107 free-ranging wolves and one captive wolf were the subjects of post-mortem investigations and sampling for molecular studies. A blood sample from one live captured wolf for telemetric tracking was also used for molecular analysis. PCR amplification targeting the 18S RNA gene revealed that 21 of 108 free-ranging wolves and one captive animal were positive for Theileria/Babesia DNA. Subsequent sequencing of a fragment of the 18S RNA gene revealed that 7/22 animals were positive for Babesia canis while the other amplified sequence were found to be identical with corresponding 18S rDNA sequences of Theileria capreoli isolated from wild deer (15/22). Haematological and cytological analysis revealed the presence of signet-ring shaped or pear-shaped piroplasms in several animals with the overall parasite burden in all positive animals assessed to be very low. Pathological investigation of the captive animal revealed fatal septicemia as a likely outcome of hemolytic anaemia. There was little or no evidence of hemolytic disease consistent with babesiosis in other animals. Conclusion: Importantly, the presence of B. canis in free-ranging grey wolves has not been described before but has been reported in a single fox and domestic dogs only. That B. canis infections cause disease in dogs but have little impact on wolf ...